ANALISIS PERSEDIAAN BAHAN BAKU CASSIA BROKEN UNTUK MEMENUHI KEBUTUHAN PRODUKSI (STUDI KASUS PT. XYZ) - Meldia Fitri; Gamindra Jauhari; Nia Syafitri (Ensiklopedia of Journal, 2020)
The supply of raw materials is a resource to meet the needs of production for the future. The inventory function is to maintain the availability of raw materials and forecasting the supply of raw materials which will be the input for future output. Problems that occur at PT. XYZ is an imbalance in the amount of inventory produced. Therefore, this study carried out an analysis of cassia broken raw material inventory to meet production needs using forecasters and safety stock. The purpose of this study was to determine the amount of cassia broken raw material inventory in 2019 and analyze the results of forecasting cassia broken raw material inventory with safety stock. The results of this study indicate that the calculation of inventory forecasting using the selected method is a linear trend with the smallest SEE of 415,079 kg and a total inventory of 24,382,177 kg.After forecasting, the supply of raw materials will be carried out using safety stock which yields 7,311,073 kg in 1 year and the average amount per month is 609,256.08 kg. By using this safety inventory the forecasting results are more accurate in accordance with the excess safety stock. so that the safety stock can be used for the next one year if at any time the raw material is delayed.